2020
DOI: 10.16949/turkbilmat.682111
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Mathematics Learning Approaches of Gifted and Non-Gifted Students

Abstract: In this study, it was aimed to investigate the mathematics learning approaches of gifted students and successful students who were not diagnosed as gifted in terms of variables of giftedness, gender, grade level, parents' profession and education level. Descriptive research model, which is one of the general survey models, was used in the study. For the 2018-2019 academic years, a total of 239 6th, 7th and 8th grade students, 84 of whom were gifted students and 155 of whom were non-gifted students, participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…In addition, the gender gap in mathematics achievement persists in some countries, while it is absent in others. On the other hand, it is revealed that while female students have a strategic and deep learning approach, male students exhibit a surface learning approach (Bulut et al, 2020;Sithole, 2018;Smith et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the gender gap in mathematics achievement persists in some countries, while it is absent in others. On the other hand, it is revealed that while female students have a strategic and deep learning approach, male students exhibit a surface learning approach (Bulut et al, 2020;Sithole, 2018;Smith et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Sungguhpun PPB dikatakan mempunyai kemampuan untuk berkembang lebih awal dalam aspek pemikiran dan penaakulan mereka daripada rakan sebaya mereka yang lain (Papadopoulos, 2020), jelaslah bahawa penglibatan kognitif, afektif dan tingkah laku mempengaruhi pencapaian pentaksiran Matematik sama ada dalam kalangan pelajar biasa ataupun PPB. Proses pengajaran dan pembelajaran Matematik yang diberikan atau ditawarkan kepada PPB penting dalam mendedahkan PPB kepada pemikiran kritis yang seterusnya mempengaruhi pencapaian pentaksiran Matematik (Bulut et al, 2020).…”
Section: Penglibatan Kognitif Afektif Dan Tingkah Laku Dan Pencapaian...unclassified
“…Students who are gifted in the field of mathematics have a high desire to study, a high level of creativity, and high motivation towards the mathematics lesson (Mingus & Grassl, 1999). In studies comparing gifted students with their peers; it is seen that gifted students have low mathematics anxiety, and their mathematics motivation, attitudes, self-efficacy, mathematics learning behaviors, and problem-solving performances are high (Bulut, Yıldız, & Baltacı, 2020;Gürel & Yetkin-Özdemir, 2019;Pajares, 1996;Wang, Huang & Hwang, 2016). Even gifted students, thanks to their ability to use induction, deduction, and analytical thinking skills, are seen to make fewer mistakes when solving non-routine problems and use different strategies to solve problems (Holton & Gaffney, 1994;Tertemiz, Do ğan & Karakaş, 2017;Vaivre-Douret, 2011;Yıldız, Baltacı, Kurak & Güven, 2012).…”
Section: Introductionmentioning
confidence: 99%